Baker & spice exceptional cakes - Lepard, Dan; Whittington, Richard
London's acclaimed bakery Baker & Spice offers a number of tempting treats - fresh apple and plum tarts, little tarts filled with rich lemon curd, chocolate and caramel cakes. This book helps the home cook to recreate some of the favourite recipes in the comfort of their own kitchen.